(untitled) (Research, Society and Development, 2021)
The addition of roots derivatives to bakery products may be a promising alternative to add value to these products. This study aimed to characterize and evaluate the effect of cassava leaves on the properties of gluten-free biscuits (GFB). The ingredients used were cassava flour, rice flour, cuí, tapioca flour, and 0 (F0), 3.69% (F1), 5.34% (F2), and 7.38% (F3) of cassava leaves (CCL). The results were evaluated by analysis of variance, followed by Scott-Knott test (p-value<0.05). The CCL presented 89.9% moisture, water activity of 0.98, and 2.75% protein; tryptophan was the limiting amino acid. No significant differences were observed between the F0-control and those made with the addition of CCL, which presented moisture and Aw below 3% and 0.30, and hardness between 45 to 60 N. The sensory acceptance scores were greater than 6, which indicates that it is possible to increase the added value of CCL in bakery products. The use of cassava leaves in biscuits showed good technological and sensory characteristics, making it possible to be an ingredient from regional by-products that can favor sustainable development, respect the concept of regionalization, and add income and employment.